Implementation of the Monitoring Center for Prevention (MCP) Program in the Regional Inspectorate of the Province of North Sulawesi - Rondonuwu, Marsela Elsa; Masengi, Evi Elvira; Bulo, Laurens (Technium Social Sciences Journal, 2025)
The purpose of this research is to find out, analyze, and describe the implementation and determinant factors that exist in the Monitoring Center For Prevention (MCP) Program at the Regional Inspectorate of North Sulawesi Province. This research uses qualitative research methods. The results showed that first, the Capacity of Government Internal Supervisory Apparatus (APIP); In the implementation of supervision in the regional inspectorate, functional APIP for the first level is still lacking, functional competency improvement of APIP has not been fulfilled, and the budget for increasing APIP capacity is still lacking. Second, Institutional Strengthening; The filling of inspector and irbansus positions in the regional inspectorate is in accordance with procedures and the availability of supporting facilities for the implementation of supervision is not sufficient. Third, Control and Supervision; Forms of control and supervision from the Regional Inspectorate of North Sulawesi Province are the availability of media for handling public complaints, namely through the SP4N report application, telephone numbers to contact, websites, emails and can be brought directly to the inspectorate office. Anti-corruption socialization has been carried out aimed at the executive, namely the chairman, deputy and members of the DPRD, regional officials and their staff, village heads and village officials and the community. Determinant factors are that the budget for the implementation of supervision is still lacking, only getting 0.26 of the APBD which should be 0.9 of the APBD. The supporting facilities and infrastructure available in the implementation of supervision are inadequate, the filling of the first functional auditor position is not in accordance with the procedure.